Characteristics of Slice Jam Produced by Ratio of Cocoa Fruit Juice and Mulberry and Carrageenan Addition - Rosida; Putri, Alimacyntia Listivani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Slice jam is a modification of jam from a spreadable form to a jam in the form of slice, shiny and non-sticky. The slice jam has shaped into the surface of bread to make it more practical. Main ingredients for the slice jam in this study is cocoa flesh with mulberry added to increases its color. To make the slice jam firm, hydrocolloids in the form of carrageenan is added. Another ingredients added are sugar, CMC and citric acid. The goal of this study is to analyze the effect of the ratio of cocoa fruit juice: mulberry with the addition of carrageenan on the characteristics of slice jam, and to determine the best treatment combination from these variations. The method used was a Completely Randomized Design (CRD) factorial pattern with Factor I, the ratio of cocoa juice: mulberry (95:5, 90:10, 85:15) and Factor II, the addition of carrageenan (3%, 4%, and 5%). The data obtained were analyzed using ANOVA followed by a DMRT further test at the 5% level. The results of the study showed a significant interaction (p?0.05). Slice jam using the ratio of cocoa fruit juice: mulberry (85:15) with the addition of 5% carrageenan is the best treatment with the characteristics of water content 33.87%; total sugar 43.94%; pH 3.61; antioxidant activity DPPH 74.04%; vitamin C 14.58 mg/100 g; water activity 0.736; hardness 83.39 gf. The resulting organoleptic properties including color, aroma, taste, and texture are 4.08 (like), 2.84 (dislike), 4.12 (like), 3.6 (like).